2022
DOI: 10.3389/fevo.2022.984056
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of extraction protocol performance on degraded mammalian museum specimens

Abstract: The extraction of nucleic acids is one of the most routine procedures used in molecular biology laboratories, yet kit performance may influence the downstream processing of samples, particularly for samples which are degraded, and in low concentrations. Here we tested several commercial kits for specific use on commonly sampled mammalian museum specimens to evaluate the yield, size distribution, and endogenous content. Samples were weighed and had approximately equal input material for each extraction. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Overall, these observations suggest that specimen preparation/storage by the collectors might have a greater impact on DNA quality than their age or the museum where they have been curated. These observations are in contrast with other studies that have statistically tested and found an effect of specimen age on DNA content or UCE recovery (Abreu et al, 2022; Hawkins et al, 2022).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Overall, these observations suggest that specimen preparation/storage by the collectors might have a greater impact on DNA quality than their age or the museum where they have been curated. These observations are in contrast with other studies that have statistically tested and found an effect of specimen age on DNA content or UCE recovery (Abreu et al, 2022; Hawkins et al, 2022).…”
Section: Resultscontrasting
confidence: 99%
“…Recent advances in high throughput sequencing in combination with natural history collection specimens provide a new, promising opportunity for the study of the IOK biogeographic transition (Hawkins et al, 2022; Lim et al, 2020; Mason et al, 2019; Patel et al, 2017). In this research, mitgenome evidence revealed deep phylogenetic breaks within each of our three study taxa across the IOK s.l .…”
Section: Discussionmentioning
confidence: 99%
“…obs. and, e.g., Hawkins et al, 2022;McDonough et al, 2018). The extraction buffer was freshly prepared to contain 150 μL Tris-HCL (20 mM), 150 μL NaCl (20 mM), 3 mg of SDS, 12 μL DTT (1 M) and 20 μL proteinase K (600 mAU/ml) per sample.…”
Section: Molecular Analysis and Genome Assemblymentioning
confidence: 99%
“…Museum collections are the most important archives of biodiversity on Earth and are used increasingly for various studies, including identification (Wannell et al, 2020), phylogenetics (Hawkins et al, 2016; Kehlmaier et al, 2020), population genomics (Castañeda‐Rico et al, 2022; Fry et al, 2020), conservation (Feigin et al, 2017; Jensen et al, 2022), biogeography (Irestedt et al, 2006; Lynch Alfaro et al, 2012; Pedersen et al, 2016), and ecology (Muff et al, 2023; Orlando & Cooper, 2014). However, molecular analysis of old museum material remains challenging because the historical DNA (the term coined by Raxworthy and Smith (2021) and adopted throughout this study) has degraded, is fragmented, and is of low quantity (Hagelberg et al, 2015; Hawkins et al, 2022). Nevertheless, there is a growing number of studies that have successfully used whole genome or target‐capture sequencing methods for acquiring complete (mitochondrial) genomes from museum material (e.g., Li et al, 2015; Straube, Lyra, et al, 2021), including of formalin‐preserved specimens (Hahn et al, 2022; Hykin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the majority of research investigating how to maximize the recovery of genetic data from non-ancient museum specimens has focused on the influence of DNA source or extraction method on DNA yield (Hahn et al, 2022; Hawkins, Flores, McGowen, & Hinckley, 2022; McDonough et al, 2018; Pacheco et al, 2022; Straube et al, 2021; Tsai et al, 2020; Zacho et al, 2021). However, DNA yield does not necessarily predict sequencing success or efficiency (McDonough et al, 2018; Straube et al, 2021; Zacho et al, 2021) because it is not possible to estimate the proportions of endogenous versus exogenous extracted DNA.…”
Section: Introductionmentioning
confidence: 99%